The HDL handbook : biological functions and clinical implications - Komoda, Tsugikazu (Academic Press, 2014)
The HDL Handbook: Biological Functions to Clinical Implications brings laboratory research in HDL from bench to bedside in this needed resource for researchers and clinicians studying cholesterol, lipids, epidemiology, biochemistry, molecular medicine, and pathophysiology of cardiovascular diseases. In addition, researchers and clinicians working with an aging population, corporate researchers, post-doctorates; medical students and graduate students will find this publication useful because the scope of coverage includes basic science, genetics, epidemiology, and treatment of HDL cholesterol as well as potential targets to modify HDL cholesterol. Provides bench-to-bedside coverage of HDL with thorough coverage of basic science, genetics, epidemiology, and treatment Presents a complete update with six new chapters on the latest advances in HDL cholesterol research with international perspective New chapters on proteomics, clinical impact of LCAT in HDL metabolism, and an in-depth discussion of potential targets to modify HDL provide a translational reference for clinicians.